(untitled) (Al-Qamar, 2023)
Orientalists refer to those non-Muslim intellectuals, whether they belong to East or West, whose aim is to gain possession of the sciences and arts of Muslims and raise objections to Islam. And to avenge the humiliating defeat at the hands of the Muslims in the crusades. And for this purpose, they have made the Quran, Sunnah, Hadith, Seerat and Islamic history as their special target and use different tactics to make them suspicious. The Isthiraq movement started in the 8th century AD. The majority of those who started this movement consisted of Monks and Priests in which there were those from the East and also from the West, this movement has been busy with its work for twelve hundred years. The main objective of this movement is to counter the threat of Islam.